Kesan pengudaraan dan pencairan ke atas penghasilan bioetanol secara selanjar dalam bioreaktor padat oleh Saccharomyces cerevisiae - Ng, Kee Wee; Aidil Abdul Hamid,; Mohd Sahaid Kalil,; Wan Mohtar Wan Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Stability of cell growth was achieved continuously at a steady state in a packed-bed bioreactor. The highest productivity of ethanol was achieved (0.02 g/L/h) when 0.003 vvm was employed. The productivity of bioethanol increases when dilution rate increases. The highest production of 0.037 g/L/h was recorded when the dilution rate (D) was at 0.05 per hour. The production of bioethanol was sucessfully maintained in a non 100% anaerobic condition. The best aeration for the continous production of bioethanol in a condition of steady state growth was at an aeration rate of 0.003 vvm.